Cytotoxicity of Shiga toxin for primary cultures of human colonic and ileal epithelial cells. - Moyer, M P (1987)
Shiga toxin purified from Shigella dysenteriae 1 was cytotoxic to cultured epithelial cells from human colon and ileum. The cytotoxicity, which affected only about 50% of treated cells, was neutralized by rabbit antiserum monospecific for Shiga toxin and mediated by protein synthesis inhibition.